The Impact of Anthropogenic Heat on Formation of Urban Heat Island and Energy Consumption Balance - Nurakmal, Abdullah@ Goh Tuo Ho; Shahmohamadi, P.; Che-Ani, A. I.; Khairul Nizam, Abdul Maulud; Norngainy, Mohd Tawil (Hindawi Publishing, 2011)
This paper investigates the impact of anthropogenic heat on formation of urban heat island (UHI) and also determines which factors can directly affect energy use in the city. It explores literally the conceptual framework of confliction between anthropogenic heat and urban structure, which produced UHI intensity and affected energy consumption balance. It then discusses how these two factors can be affected and gives implication to the city and then focuses on whether actions should be taken for balancing adaptation and mitigation of UHI effects. It will be concluded by making the three important strategies to minimise the impact of UHI on energy consumption: landscaping, using albedo materials on external surfaces of buildings and urban areas, and promoting natural ventilation.